Prevalence of Oral Lesions in Relation to Tobacco and Alcohol Habits Using VELscope - A Retrospective Study - Kameswara Rao Ayyagari; N Ratna Kumari; Padmavathi Bolem; Sunil Kumar Komanapalli; Sumit Majumdar; Parameswar Peela (Indian Journal of Dental Research)
Background: Tobacco consumption, in its various forms, is a primary cause of significant health conditions such as oral premalignant disorders and oral cavity carcinoma. This study investigates the current prevalence of oral lesions in the region, utilizing modern techniques to analyze the impact of tobacco on oral health. Aims and Objectives: To evaluate the prevalence of oral lesions associated with tobacco and alcohol use, employing VELscope technology for assessment, and to evaluate the benefits of this recent technology in the assessment process. Materials and Methods: Patients with a history of tobacco and alcohol use were included based on specific criteria. The study documented oral manifestations, chief complaints, VELscope findings, and histopathological diagnoses, and correlated these data. Statistical analysis was conducted using IBM SPSS Statistics Version 21, with descriptive statistics (percentages, mean, and standard deviation) and categorical data comparisons (Chi-square test). A significance level of P ≤ 0.05 was used. Results and Conclusion: The study found a notable shift from smoked to smokeless tobacco, predominantly affecting younger individuals. This highlights the need for targeted tobacco cessation efforts at the grassroots level. While VELscope can aid in diagnosis, it should not replace histopathological evaluation entirely.